2018
DOI: 10.1002/jlb.ma0318-136rrr
|View full text |Cite
|
Sign up to set email alerts
|

IRF5 regulates unique subset of genes in dendritic cells during West Nile virus infection

Abstract: Pathogen recognition receptor (PRR) signaling is critical for triggering innate immune activation and the expression of immune response genes, including genes that impart restriction against virus replication. RIG-I-like receptors and TLRs are PRRs that signal immune activation and drive the expression of antiviral genes and the production of type I IFN leading to induction of IFNstimulated genes, in part through the interferon regulatory factor (IRF) family of transcription factors. Previous studies with West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Type I IFN may also diminish DC maturation, reduce production of IL-1β, and weaken antiviral T cell immunity in AXL receptor tyrosine kinase deficient (Axl −/− ) mice during WNV and influenza infection [70]. Recent studies showed that IL-1β, IFN regulatory factors (IRF) 3, 5 and 7 are important to induce DC-mediated antivirus IFN responses against WNV infection [71][72][73].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Type I IFN may also diminish DC maturation, reduce production of IL-1β, and weaken antiviral T cell immunity in AXL receptor tyrosine kinase deficient (Axl −/− ) mice during WNV and influenza infection [70]. Recent studies showed that IL-1β, IFN regulatory factors (IRF) 3, 5 and 7 are important to induce DC-mediated antivirus IFN responses against WNV infection [71][72][73].…”
Section: Innate Immunitymentioning
confidence: 99%
“…Genetic data have revealed the relevance of IRF family members to IFN responses ( 6 10 ). IRF3 and IRF7 are two primary regulators of IFN expression downstream of signaling pathways triggered by TLRs (such as TLR3/7/9), RLRs and DNA sensors (such as cGAS) ( 1 ).…”
Section: Introductionmentioning
confidence: 99%